Abnormalities of the erythrocyte membrane - Gallagher, Patrick G (The Pediatric clinics of North America, 2013)
Primary abnormalities of the erythrocyte membrane are characterized by clinical, laboratory, and genetic heterogeneity. Among this group, hereditary spherocytosis patients are more likely to experience symptomatic anemia. Treatment of hereditary spherocytosis with splenectomy is curative in most patients. Growing recognition of the long-term risks of splenectomy has led to re-evaluation of the role of splenectomy. Management guidelines acknowledge these considerations and recommend discussion between health care providers, patient, and family. The hereditary elliptocytosis syndromes are the most common primary disorders of erythrocyte membrane proteins. However, most elliptocytosis patients are asymptomatic and do not require therapy.